Determination of average coating removal efficiency for Nd: YAG laser over three types of car coated substrate - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman; Syahrul Affandi Saidi (2014)
A technique to determine the average coating removal efficiency ( ϵ) of Cynosure Cynergy Pulse Nd:YAG laser in paint removal has been developed on national and imported car coated substrates. This paper reports on the results of studies carried out on three types of different coating thicknesses ranging from 92 – 134 μm, 196 – 450 μm and 219 – 283 μm. Alicona IFM G4 analysis was done to find the depth for each irradiated crater on three types of substrate samples using profilometer obtained. Depth (d) versus laser laser fluence (F) graph was plotted to determine the ϵ process for each substrate samples. This research paper proves the paint removal was increased with increasing of F but independence by manipulating the long pulse width (PW) and low range of repetition rate (RR).